GEODESIGN IN THE PROPOSITION OF URBAN PARAMETERS OF OCCUPATION: POSSIBILITIES OF APPLICATION OF A 3D CADASTRE IN LANDSCAPE MANAGEMENT - Roquete Ribeiro, Suellen; Mourão Moura, Ana Clara (Revista Brasileira de Cartografia, 2018)
An urban landscapeis composed by a set of many factors, and each one of them has a role in building a landscape that expresses values, cultural and social aspects of a society. This article focus on investigating possibilities to address urban landscape planning through a methodological approach that explores the urban parameter for occupation as one of the factors that shape our urban environment and landscape. The main goal is to discuss the planner'stask of decoding and translating social and cultural values to the landscape while showingsome possible outcomes from the investment in data acquisition, andthe structuration of an urban multipurpose 3D cadastre.Thus, the case study presents a Geodesign workshop which was held in the Geoprocessing Laboratory of the School of Architecture, from the Federal University of Minas Gerais (UFMG) and was attended by 13 participants. The participants were invited to propose new patterns for the land occupation through the defnition of urban parameters for an area in Pampulha region, in Belo Horizonte. The methodological process was based on Parametric Modeling for the visualization of alternative futures of urban landscape as a support for the opinion taking process promoted by the framework of Geodesign. As a result, the values and expectations from each group of representatives of the society were analyzed allowing an assimilation of the elements that interfere the most on citizens' interests for the composition of the urban land use. Extending the experience can favor a broader support for decision-making on proposition of Land Use laws as much as justify investments on the formation of 3D cadastre for municipal planning and management.